Dual-organocatalytic Michael/Michael/aldol cascade reaction for the asymmetric construction of fully-substituted cyclohexane. Issue 51 (21st December 2016) - Sun, Qiang-Sheng; Zhu, Hua; Lin, Hua; Tan, Yu; Yang, Xiao-Di; Sun, Xing-Wen; Sun, Xun
Graphical abstract: Highlights: Enatiopure fully-substituted cyclohexanes bearing six stereocenters were synthesized. Low loading dual-organocatalysts were used. Excellent stereoselectivities (>99% ee, >20:1 dr in all cases) were obtained. Abstract: An efficient cascade reaction was developed affording fully-substituted cyclohexane bearing six contiguous stereocenters via Michael/Michael/aldol sequence. This reaction was catalyzed by low loading of dual-organocatalyst, H-bond donor squaramide (0.5 mol%) and achiral secondary amine pyrrolidine (10 mol%). Good yields (up to 81%), excellent diastereoselectivities (>20:1 in all cases) and enantioselectivities (>99% in all cases) were obtained for a wide array of Michael acceptors.